Separation of Paracoccidioides brasiliensis conidia through Percoll gradients (2004)
ABSTRACT: The conidia of Paracoccidioides brasiliensis are the structures most likely to serve as the infectious propagules of this fungus. This study describes our attempts to purify conidia by eliminating mycelial fragments. Purification was attempted using discontinuous 95% and 60% Percoll gradients with densities of 1.167 and 1.107, respectively, prepared either in 0.15 mol/L PBS or 0.25 mol/L sucrose. The best results were observed with the 95% and 90% gradients in sucrose; with the former, conidial purity ranged from 70.6 to 100%, with a mean of 82.3% and a coefficient of variation (VC) of 11.7. With 90% gradients, purity was achieved between 70.4 and 92.5%. The mean in this case was 80.6% and the VC was 9.2%. The use of two consecutive 95% Percoll gradients in sucrose was tested. The recovery efficiency per plate, which averaged 2.5 /106 conidia per plate with one gradient, increased to 5.19/1.3 /106 conidia with two gradients. The use of Percoll did not affect the viability of the conidia, which was always]/90%. This method allows the preparation of a conidial sample almost free from contamination with mycelial fragments, thus facilitating quantitative determination of cause and effect in in-vivo interactions between P. brasiliensis and its hosts.